Pemanfaatan Teknologi Aquaponik Tanaman Kangkung dan Budidaya Ikan Lele dalam Ember di Desa Gelam, Kecamatan Candi, Sidoarjo - Binti Azizatun Nafi’ah; Ahmad Bagus Rohim; Desnita Mazaya Choirunisa; Fadia Hana Khairani; Fernanda Putri Jelita; Mochammad David Hardiansyah; Cyntya Dwi Permata; Sisilia Srikandi Mukti; Elvi Anggino Erzon; Reiga El Rafif; Anggie Devitasari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Aquaponics technology integrates aquaculture and hydroponics, utilizing space and resources efficiently for fish and plant cultivation. This community service program introduces aquaponics technology based on